Saving Practices and Economic Performance: A Zimbabwean Case 1980–2015 - Olubukola, Otekunrin Adegbola; Kudzanai, Matowanyika; Shepard, Makurumidze; Thomas, Bhebhe; Obert, Sifile (Asian Economic and Financial Review, 2021)
Savings are current income not spent but kept for future use or the accumulation of financial and non-financial assets. They are mobilized by the financial sector, which allocates them for productive use in the economy. This paper sought to examine the impact of saving practices on the performance of the economy in Zimbabwe from 1980 to 2015. A mixed research approach was used to establish the effect of saving practices on the performance of the economy. Both primary and secondary data were employed for analysis and testing of hypotheses. Hypothesis testing, correlation analysis and regression analysis were used to examine the impact of saving practices on the performance of the economy using some macroeconomic variables. Two hundred depositors randomly selected from various banking institutions from the ten provinces and 114 key informants were used in the investigation. Secondary data on gross domestic product (GDP), total deposits, total liabilities, gross capital formation and net exports were used in the examination of saving practices. The study found that savings were always below the average and the Zimbabwean majority across genders had a formal bank or mobile account. Predominantly, savings are used for transactional purposes, thus creating a wasteful economy. Apart from product/service broadening and deepening, there is a need for robust legal and policy frameworks that will promote a savings culture.